Computer mediated communication: facilitating online learners as members of a community of practice - Ab Jalil, Habibah; Ismail, Ismi Arif; Wong, Su Luan; Ab. Aziz, Sidek (2007)
With the help of social network analysis and the concept of 'community of practice', this paper reports on the patterns of interaction and participation of tutor and students discussion through computer-mediated communication (CMC). The descriptions cover the nature of participation; tutor-student and student-student interactions; the' nature of assisted performance; and the social network in the particular tasks. This paper offers an analysis of interaction patterns between tutor-student and student-student in different nature of tasks. Analysis shows that the pattern of assisted performance by a peer or the tutor could depend one or more of these factors: type of task (the nature of task initiated), group formation (either one whole big group or small working group) and the tutor management (the degree of tutor involvement in responding to students' posting).